On the origin of the electroactive poly(vinylidene fluoride) β-phase nucleation by ferrite nanoparticles via surface electrostatic interactions - Martins, Pedro (2012)
Flexible multiferroic 0-3 composite films, comprising NiFe2O4 and CoFe2O4 ferrite nanoparticles in a polyvinylidene fluoride (PVDF) matrix, have been prepared by solvent casting and melt crystallization to investigate the polymer β-phase nucleation mechanism. Infrared spectroscopy confirms the nucleation of the polymeric electroactive β-phase with the addition of both ferrites, although the loading of ferrite 10 nanoparticles needed to obtain the highest amount of β-phase was found to be one order of magnitude higher in the NiFe2O4/PVDF nanocomposites. Transmission electron microscopy imaging and thermogravimetric analyses indicate the formation of an interface in the nanocomposites with the β-phase nucleation. It is shown that the essential factor for the nucleation of the β-phase in the ferrites/PVDF nanocomposites is the static electric interaction between the magnetic particles with a negative zeta 15 potential and the CH2 groups having a positive charge density.